Fat-1 gene modulates the fatty acid composition of femoral and vertebral phospholipids - Lau, Beatrice Y.Y; Ward, Wendy E; Kang, Jing X; Ma, David W.L (Applied physiology, nutrition, and metabolism, 2010)
Dietary polyunsaturated fatty acid (PUFA) incorporation into bone may alter its metabolism through changes in the fatty acid composition of membrane phospholipids. Alteration of the membrane phospholipid fatty acid composition may influence bone cell signalling and, potentially, bone mineralization. The objective of this study was to use the fat-1 mouse, a transgenic model that synthesizes n-3 from n-6 PUFA, to determine if the fat-1 gene modulates the fatty acid composition of femoral and vertebral phospholipids, and if so, whether the fatty acid levels would correlate with bone mineral density (BMD) at both skeletal sites. Male and female wild-type and fat-1 mice were fed an AIN93-G diet, containing 10% safflower oil, from weaning to 12 weeks of age. The fatty acid composition of femoral and vertebral phospholipids was measured by gas liquid chromatography. At 12 weeks of age, phosphatidylcholine, phosphatidylethanolamine, and phosphatidylserine fractions in the vertebrae of fat-1 mice had a significantly lower n-6/n-3 ratio than wild-type mice (p < 0.05). In fat-1 femurs, these fractions, along with phosphatidylinositol, had a lower n-6/n-3 ratio than wild-type mice (p < 0.001). Docosahexaenoic acid (DHA) was positively correlated with BMD in all fractions in the vertebrae, and in phosphatidylinositol and phosphatidylserine in the femur (p < 0.05). Overall, the fat-1 gene resulted in changes in the fatty acid composition of both femoral and vertebral phospholipids. Significant correlations between DHA and BMD may indicate a positive effect on bone mineralization.